An Investigation on Factors Affecting Financial Crisis in Iran's Non-Governmental Universities to Develop a Strategy to Deal with It - Ebrahim AliMohammadiAsl; Alireza BafandehZende; Houshang Taghizade (Comparative Education Society of Iran ( CESIR), 2021)
Private and semi-public universities in Iran have faced several challenges in recent years. The purpose of study was to identify the factors affecting financial crisis in non-governmental universities and to develop a strategy to deal with it with emphasis on the situation of the Islamic Azad University of Tabriz. The method of study was exploratory mixed method and data collection tools in the qualitative part was semi-structured interview and in the quantitative part, a researcher-made questionnaire. The statistical population for the qualitative section included the president, vice chancellors and staff managers of the university (as an expert group) who were selected by targeted sampling method (12 people). In the quantitative part of the research, 350 faculty members and university students were selected through relative stratified sampling. Exploratory and confirmatory factor analysis tests were used for data analysis and causal diagrams for formulating strategy. The findings of the research based on two scenarios of "confrontation strategy" showed that if the retirement rate of university staff increased, the upward trend of university expenses will stop and then decrease. Also, by increasing the research budget, it is possible to improve university ranking and student enrollment rate. According to the findings, planners of private and non-governmental universities are recommended to increase the retirement rate of employees in a short period of time (5 years). It is also recommended to increase the relationship between the university and industry and commerce to increase research income.